Application Of "Memory Titanol Spring" During The First Molar Extraction Space Closure - Aynur Aras; Yahya Tosun (Galenos Yayinevi, 1999)
In this article, during the first molar extraction space closure in a high angle open bite case, the application of "Memory Titanol Spring" for mesial translation without extrusion of the second molars is described. After levelling, Memory Titanol Springs were inserted posteriorly into the second molars' auxiliary tubes and anteriorly into the cross tubes that are crimped on .016" x .022" stainless steel continuous wire between canines and first premolars. Mesial movement was accomplished with 160 gm and 150 gm intramaxillary elastics on upper and lower arches respectively. This method is found to be effective in closing the first molar extraction space by translational movement without extrusion of the second molar.